Durability of running economy: differences between quantification methods and performance status in male runners - Zanini, M.; Folland, J. P.; Blagrove, R. C. (Medicine & Science in Sports & Exercise, 2024)
Introduction Running economy (RE) deteriorates during prolonged running, although the effect of measuring energy cost (EC) or oxygen cost (OC) on the magnitude of these changes has not been investigated. Similarly, it is unknown if runners` performance level may influence the deterioration of RE during prolonged running. The aims of this study were to compare changes in EC and OC measurements of RE during a prolonged run in a large cohort of well-trained male runners, and to compare changes between runners of high and low performance standard.